Sistem Pakar Diagnosa Penyakit Diabetes Melitus Menggunakan Metode Certainty Factor - Hendrimaradona; Lena; Kikiyasdomi; Dona (Universitas Harapan Medan, 2021)
Diabetes Mellitus A chronic (chronic) disease in the form of a metabolic disorder characterized by the appearance of wounds accompanied by a discharge that smells bad from the feet, type 1 diabetes mellitus, type 2 diabetes mellitus, and gestational diabetes mellitus, therefore it must be treated immediately since early appearance of symptoms. Advances in expert systems can overcome this problem, namely by designing a web-based computer system that uses databases and programming languages ??such as PHP-MySQL so that it can help diabetes mellitus patients to diagnose the disease. The purpose of this study is to build an expert system for diagnosing diabetes mellitus based on a web. An expert system that adopts the knowledge of an expert so that it can solve a problem like an expert. The reason for using this certainty factor is because it can provide fairly accurate results obtained from calculations based on the selected symptoms, is able to provide answers to problems that are not certain of the truth such as the problem of diagnosing Diabetes Mellitus and with this method it gives an expert confidence by providing a confidence value in accordance with expert knowledge. The analysis and design of the system used are Context Diagrams, Data Flow Diagrams, Entity Relationship Diagrams and Flowcharts. The system will give an order in the form of selecting the symptoms experienced, namely what symptoms are experienced. Then the patient chooses the symptoms experienced. The system will provide diagnostic results based on the symptoms experienced by the patient. The results of the diagnosis are the type of diabetes mellitus experienced and the treatment solution and what percentage of the patient's likelihood of suffering from the disease